Evaluación de la respuesta de cacao CCN-51 a plena exposición solar a las aplicaciones de Azufre (S) y Magnesio (Mg) en la zona de Zapotal, Provincia de Los Ríos. - Vélez Ruiz, Josselyn Noemí (2018)
The research took place at the "Gloria Haymee" farm in the Zapotal area, Los Ríos Province. The experimental sites coordinates are 1 ° 23'30.5 '' (S.L) and 79 ° 23'44.4 '' (W.L). The objective of the study was to evaluate the response of the CCN-51 cocoa crop, growing at full sun exposure to the application of S and Mg. Field treatment distribution followed a. Complete Block randomized design with three repetitions. Means were compared using the Duncan test (p = 0.05). Orthogonal contrasts were done to look for possible statistical differences between the levels of S and Mg hidden by the experimental error. The variables selected for the study were: number of pods per plant, healthy pods, cherelle wilt fruits, diseased pods, pod´s weight, bean number, fresh weight, Dry bean yield in kg ha-1 was calculated from the fresh bean weight. The beans macro and micronutrients contents was determined for selected treatments. An economic analysis based on yield output as affected by treatments was conducted. No significant differences in the selected variables, including disease incidence, due to the effect of S and Mg fertilization were observed. B/C relationship and profitability were the highest for the control treatment. Keywords: fertilization; sulfure; magnesium; yield; diseases.